2023
DOI: 10.3390/rs15030669
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cropland Abandonment in Southern China from 1992 to 2020 Based on the Combination of Phenological and Time-Series Algorithm Using Landsat Imagery and Google Earth Engine

Abstract: Cropland abandonment is one of the most widespread types of land-use change in Southern China. Quickly and accurately monitoring spatial-temporal patterns of cropland abandonment is crucial for food security and a good ecological balance. There are still enormous challenges in the long-term monitoring of abandoned cropland in cloud and rain-prone and cropland-fragmented regions. In this study, we developed an approach to automatically obtain Landsat imagery for two key phenological periods, rather than as a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Su et al developed an algorithm based on phenology and time series and, after analyzing satellite imagery from Google Earth Engine, highlighted that abandoned lands in Guangdong Province have consistently measured around 500,000 hectares. Post-2000, due to the rapid urbanization of Guangdong, the rate of land abandonment has been increasing yearly [63]. In 2021, the Guangdong provincial government announced a cultivated land area of 28,480,000 mu, equivalent to 1,898,667 hectares, with a land abandonment rate reaching 26%.…”
Section: Ranking Of Per Capita Gross Regional Productmentioning
confidence: 99%
“…Su et al developed an algorithm based on phenology and time series and, after analyzing satellite imagery from Google Earth Engine, highlighted that abandoned lands in Guangdong Province have consistently measured around 500,000 hectares. Post-2000, due to the rapid urbanization of Guangdong, the rate of land abandonment has been increasing yearly [63]. In 2021, the Guangdong provincial government announced a cultivated land area of 28,480,000 mu, equivalent to 1,898,667 hectares, with a land abandonment rate reaching 26%.…”
Section: Ranking Of Per Capita Gross Regional Productmentioning
confidence: 99%
“…The results showed that the abandoned cropland was mainly abandoned at once, among which 23.61 million hectares (89.20%) had been abandoned once, 2.75 million hectares (10.39%) had been abandoned twice, and 0.11 million hectares (0.41%) had been abandoned three times or more. Multiple abandonment requires multiple reclamation, each time requiring large investments for treatment and restoration, wasting agricultural input costs [39]. To reduce these negative impacts, the soil and ecological environment can be protected by adopting circular and sustainable agriculture methods, such as rational fertilization, crop rotation, and afforestation.…”
Section: Characteristics Of the Frequency Of Cropland Abandonmentmentioning
confidence: 99%
“…The satellite remote sensing technology has been widely employed in the extraction of cropland parcels. Various satellites, such as the Moderate-Resolution Imaging Spectroradiometer (MODIS) [10][11][12], Landsat [13][14][15][16], Satellite Pour l'Observation de la Terre (SPOT) [17,18], Sentinel [19][20][21][22], WorldView [23], and QuickBird [24], have achieved good results. Some studies have performed research in cropland extraction in southern China.…”
Section: Introductionmentioning
confidence: 99%